Prediksi IHSG dengan Model Garch dan Model Arima - Nachrowi, Nachrowi D.; Usman, Hardius (Jurnal Ekonomi dan Pembangunan Indonesia, 2007)
This study search for proper models to forecast Jakarta Composite Index (JCI) and then compare their forecasts. The stock index from strong markets, like Dow Jone Industrial Average (DJIA) and NIKKEi, as well as the index from regional markets, like SET, are expected to have strong influences on JCI. More specifically, it is expected that SET will be able to explain the realocation of short term Jund from Thailand to Indonesia through capital market due to unfavour political situation in Thailand. Other than that, exchange rate is also expected to have effect on JCI movements. By using the daily data from January 3, 2005 to January 2, 2006, the study found that the proper models to be used to forecast JCI are GARCH (2,2) Model and ARIMA (1,1,0) Model. The empirical results showed that the forecast from ARIMA Model is superior to that of GARCH Model.